PENGARUH TINGKAT INVESTASI DAN PDRB TERHADAP TINGKAT PENYERAPAN TENAGA KERJA SEKTOR PERTANIAN DI KABUPATEN/KOTA PROVINSI ACEH: APLIKASI DATA PANEL ARDL - Miftahul Jannah; Ernawati Ernawati (Fakultas Ekonomi dan Bisnis UNSYIAH, 2023)
AbstractThis study was aimed to determine how deep the contribution of the agricultural sector in Aceh Province to the involvement of workforce. The data used in this study are secondary data and panel data consisting of time series data from 2011-2021 and cross section data of 9 districts and cities in Aceh Province which were obtained from Badan Pusat Statistik (BPS), Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Aceh (DPMPTSP) and Badan Koordinasi Penanaman Modal (BKPM). The analytical method used in this study is ARDL panel. The results showed that in the short term of PDRB variable and investment level variables had a negative and insignificant effect on the involvement of employment in the agricultural sector. In the long term, the variables of PDRB and the level of investment have a positive and significant effect on the involvement of employment in the agricultural sector.Keywords: PDRB of the agricultural sector, the level of investment, and workforce involvement.